Pathological and Surgical Outcomes of Retropubic Radical Prostatectomy in an Academic Center: A Contemporary Study - Prudhomme, Thomas; Roumiguié, Mathieu; Péricart, Sarah; Doumerc, Nicolas; Lesourd, Marine; Patard, Pierre Marie; Gamé, Xavier; Soulié, Michel; Thoulouzan, Matthieu; </g (Archives of Clinical and Biomedical Research, 2020)
Purpose: To report the peri-operative, pathological and oncological outcomes of a contemporary series of open retropubic radical prostatectomy (RRP), performed by one experienced surgeon on RRP technique developed by Barré C. Methods: We analyzed data of consecutive patients who underwent an RRP as first-line treatment for localized prostate cancer, from January 2014 to December 2018, in single French academic center. a) Benign capsular incision (BCI) and b) Benign glandular tissue incision (BGTI) were defined as: presence of inadvertent intraprostatic incisions into benign glandular tissue in regions where capsule was a) present and b) absent. Results: Overall, 312 patients were included. The rates of pT1c, pT2 and pT3 were 0.3% (n=1), 49.0% (n=153) and 50.6% (n=158), respectively. The rates of non-nerve sparing surgery (NSS), unilateral NSS and bilateral NSS were 20.5% (n=64), 31.4% (n=98) and 48.1% (n=150). The median length of hospital stay was 4.0 (3.0-5.0) days and the median estimated blood loss was 250.0 (150.0-180.0) milliliters. The total positive surgical margin (PSM) rate was 11.9% (n=37). The total pT2 PSM and pT3 PSM rates were 0% and 23.4% (n=37) and achieved a statistical difference (p<0.001). The total BCI and BGTI rates were 1.6% and 9.0 %. Biochemical recurrence occurred in 29 (9.3%) patients at median 1.0-year of follow-up. Conclusion: Retropubic radical prostatectomy performed as previously described by Barré C., is reproductible and ensures optimal surgical results, in a predominantly population of intermediate-risk prostate cancer and high-risk prostate cancer. <gdiv></gdiv>